The Contribution of Financial Literacy on Decision in Sharia Stock Investment Profit Anywhere Platform: SEM-PLS Analysis - Akbar, Tubagus; Ma'mun, Saepul; Sutira, Andri; Solihin, Dadin (Universitas Siliwangi, 2025)
Introduction to The Problem: Islamic stock investments have experienced significant growth in line with the development of digital platforms such as Profits Anywhere. However, rational investment decisions are still influenced by the level of financial literacy among investors.Purpose: This study aims to analyze the effect of financial literacy on Islamic stock investment decisions using the Profits Anywhere platform.Methodology: The method used was quantitative with a Partial Least Square-Structural Equation Modeling (PLS-SEM) approach. The respondents in this study were 149 Islamic economics students from STAI Pelita Nusa who were selected randomly.Findings: The results show that the indicators have good convergent validity with outer loadings above 0.70 and AVE above 0.5. The reliability test shows strong internal consistency. The research model has an R-square of 0.412 and an F-square of 0.256, indicating a significant effect of financial literacy on Islamic stock investment decisions. Hypothesis testing yielded a p-value of 0.002 and a t-statistic of 4.734, proving that financial literacy has a positive effect on investment decisions in Islamic STOCK. The implications of this study underscore the importance of improving technology-based financial literacy and education on the Profits Anywhere platform.Paper Type: Research Article